Sovereign Risk and Bank Risk-Taking - Anil Ari (Oesterreichische Nationalbank (OeNB), 2015)
In European countries recently hit by a sovereign debt crisis, the share of domestic sovereign debt held by the national banking system has sharply increased. This paper examines the banking equilibrium in a model with optimizing banks and depositors, deriving implications for economic vulnerability to crisis and policy design. It shows that under-capitalized banks have an incentive to gamble on domestic sovereign bonds when they expect to suffer from non-bond losses in the aftermath of sovereign default. Depositor reactions to insolvency risk impose discipline, but also leave the economy susceptible to self-fulfilling shifts in sentiments, where sovereign default also causes a banking crisis. In an adverse equilibrium, sovereign risk shocks simultaneously raise bank funding costs and drive banks to increase their purchases of domestic debt, crowding out bank lending. Subsidized loans to banks, similar to the ECB's non-targeted longer-term refinancing operations (LTRO), strengthen gambling incentives and may even eliminate the good equilibrium. Targeted interventions have the capacity to eliminate adverse equilibria.
Keywords: E44; E58; F34; G21; H63; 330; Sovereign Debt Crises; Bank Risk-Taking; Financial Constraints; Eurozone